Driving school student management system - Tengku Diyana, Tengku Ibrahim (2005)
There are only a few driving schools are operating around Pahang,but the total of the driving school cannot manage the number of customers who want to learn driving that are increasing each year.Most of the school company does not apply any computerized system to manage their business properly.All of the process of registering new student is done in traditional way which is using paper forms. The management of student progress is also written in log book. The ways the company manage their business are too complicated.Worst case comes when there are like a hundred of student to be managed in an hour, while the company Is currently short of workers to find each customer document to be updated.As a result,a system needs to be developed to replace the current system and enhance the company's performance of management.Driving School Student Management System is proposed to handle this job.The system is developed to handle the process of secured login using Rijndael symmetric encryption algorithm,registering new student,searching a student profile and also searching for student progress to be updated using simple linear sequential search algorithm.The expected result from this system is to get the correct output for each function and system is robust and free of error.